2022
DOI: 10.1186/s13578-022-00796-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing profiles reveal dynamic signaling and glucose metabolic features during bone marrow mesenchymal stem cell senescence

Abstract: Background Stem cell senescence is considered as a significant driver of organismal aging. As individuals age, the number of stem cells is declined, and the ability to proliferate and survive is also weakened. It has been reported that metabolism plays an important role in stem cell self-renewal, multilineage differentiation, senescence and fate determination, which has aroused widespread concerns. However, whether metabolism-related genes or signalling pathways are involved in physiological ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that gene expression related to metabolic processes and protein/nucleotide biosynthetic processes are markedly downregulated in BM-MSCs from aged donors, supporting the critical role of metabolism in regulating stem cell senescence. 63 KEGG pathway analysis further revealed a significant upregulation of biosynthesis of unsaturated fatty acids pathways in the brachial-treated group, which has been previously reported to be enriched in young, healthy MSCs (SI Fig. 6) .…”
Section: Resultssupporting
confidence: 57%
“…Previous studies have demonstrated that gene expression related to metabolic processes and protein/nucleotide biosynthetic processes are markedly downregulated in BM-MSCs from aged donors, supporting the critical role of metabolism in regulating stem cell senescence. 63 KEGG pathway analysis further revealed a significant upregulation of biosynthesis of unsaturated fatty acids pathways in the brachial-treated group, which has been previously reported to be enriched in young, healthy MSCs (SI Fig. 6) .…”
Section: Resultssupporting
confidence: 57%
“…In our previous study, cell surface antigens were used to identify obtained MSCs by flow cytometry. We found that serial expanded MSCs are positive for mesenchymal progenitor markers including CD44, CD90, and CD105, and negative for CD31 and CD45 [ 32 ]. Nevertheless, MSCs at LP presented attenuated osteogenesis compared with EP MSCs [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…MSCs were obtained according to a previously described method [ 16 , 17 , 32 ]. Primary MSCs derived from healthy, 1–2-month-old male Wistar rats were isolated by the whole bone marrow adherent method.…”
Section: Methodsmentioning
confidence: 99%
“…What’s more, an examination of BM-MSCs from old and young rats revealed 868 differentially expressed genes (DEGs) that were up-regulated and 2006 that were down-regulated. A high expression of DEGs might be involved in cell differentiation and growth factor binding, whereas down-regulated DEGs appear to be involved in metabolism [ 55 ]. Circular RNAs(circRNAs) may compete with microRNAs (miRNAs) for the ability to stabilize or translate target RNAs, and thereby affect gene expression.…”
Section: Defects In Mscs and Msc Niches During Agingmentioning
confidence: 99%